2013
DOI: 10.1371/journal.pone.0054801
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between LTR Methylation and gag Expression of HIV-1 in Human Spermatozoa and Sperm-Derived Embryos

Abstract: ObjectiveStudying the methylation status of long terminal repeats (LTR) and its relationship to gag expression of HIV-1 in order to explore regulation mechanism of HIV-1 gene expression in vertical transmission from sperm to embryo.Methods/Principal FindingsSperm samples were collected from a healthy donor and seven patients with HIV/AIDS. Zona-free hamster ova were fertilized by donor’s spermatozoa transfected with pIRES2-EGFP-LTR-gag and patient’s spermatozoa to obtain zygotes and 2-cell embryos, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
(40 reference statements)
2
8
0
1
Order By: Relevance
“…The similar results were also found by Martinez-Colom et al 35 . These data are in agreement with the other studies which correlated the DNA methylation status in 5′-LTR to transcriptional silencing 23, 24, 25, 49. Furthermore, we found that the repression of HIV-1 expression caused by ZF2-DNMT1 was stable and could be maintained through several cell divisions, which was consistent with the results published by Blancafort et al 45, 47.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The similar results were also found by Martinez-Colom et al 35 . These data are in agreement with the other studies which correlated the DNA methylation status in 5′-LTR to transcriptional silencing 23, 24, 25, 49. Furthermore, we found that the repression of HIV-1 expression caused by ZF2-DNMT1 was stable and could be maintained through several cell divisions, which was consistent with the results published by Blancafort et al 45, 47.…”
Section: Discussionsupporting
confidence: 93%
“…DNA methylation of CpG islands in the promoter region of a gene plays a significant role in regulating mammalian gene expression. DNA methylation of HIV-1 5′-LTR has been attributed to HIV-1 transcription silencing in in vitro and in vivo studies 20, 21, 22, 23, 24, 25, 26, 27. In addition, DNA methylation patterns are inheritable to the progeny and can perform long-term stable gene suppression by methylating the targeted genes 28, 29, 30, 31, 32, 33.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings imply that transducing spermatozoa directly with pseudotyped lentiviral vectors would be a very powerful tool, not only for the study of early embryonic development, sperm physiology, transgenesis and fertilisation processes, vertical viral gene transmission [31–33] and epigenetics studies, but also in the development of large‐animal transgenics for production of therapeutically important proteins.…”
Section: Discussionmentioning
confidence: 92%
“…Several techniques are currently used to produce transgenic mammalian embryos, including pronuclear microinjection [9] , SCNT [10] , sperm mediated gene transfer [11] and intracytoplasmic sperm injection (ICSI)-mediatedgene transfer [12] . However, the mechanisms involved are not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…After transgene incorporation into a pronucleus, exogenous DNA can be integrated into the host genome mainly as result of the activity of DNA repair machinery associated with replication [10,11] . The early integration of the exogenous DNA into the host genome is a critical step for homogeneous transgenic embryo production, followed by parthenogenic activation [9][10][11] . In the present study, the results indicate that Ca 2+ concentration significantly affected the efficiency of ICSI embryos expressing EGFP regardless of electro-activation.…”
Section: Discussionmentioning
confidence: 99%